A pós-graduação e o êxito profissional: análise dos egressos de 2012 a 2018 do Mestrado em Ciências Contábeis e Atuariais da Pontifícia Universidade Católica de São Paulo (PUC-SP) - Carareto, Thaís Benassi Billegas (2020)
This study evaluate the 10performance of the graduates from the Stricto Senso Postgraduate program in Accounting and Acturial Sciences at PUC-SP, named masters, from 2012 to 2018, with the objective of trace the professional profile and relate raised data, define the professional success and evaluation of productions. To carry out the research qualiquanti, of predominantly exploratory descriptive characteristic, with raised cross-sectional data by applying questionnaires structured between dichotomous questions, multiple choice, semi-open, open and likert, using the SurveyMonkey® platform a population of 151 graduates with samples of 63 respondents, collection of information from IES and Capes. As for the application of the tests, based on descriptive and inferential statistics, with chi-square, t-student test, inference by confidence interval of 95%, Kruskall – Wallis, Cochran test, logistic regression and content analysis. As for the results obtained, was possible to observe the graduate’s perception directed to the degree for academic development, where the market assigns differential that justifies the course, even though, this positioning draws attention given that the graduate declare to act in the area of interest, considering the titration responsible for your current professional activity. However, there was no migration to the exclusively academic professional activity. There is still a significant differentiation in the perception of doctors and doctoral students to masters in terms of professional mobility, lifestyle and productivity. The average overall wage increase was 55.31 percentage points. As for academic productions, the largest volume of graduate productions is given to technical productions